2018
DOI: 10.1002/ejic.201800593
|View full text |Cite
|
Sign up to set email alerts
|

Coupled High Spin CoII Ions Linked by Symmetrical Double Hydrogen Bonds: Role of a Slowly Relaxing CuII Impurity in Interrupting the CoII–CoII Exchange Interaction

Abstract: Co II and Cu II ions are two paramagnetic transition metal ions showing different relaxation rates (ν), with ν Co II >> ν Cu II . To measure the isotropic exchange constant (J) between high spin Co II ions and between Cu II ions and high spin Co II ions, we performed magnetic and EPR measurements complemented with computational calculations on pure transdiaqua-bis(picolinato-N,O)-cobalt(II) dihydrate (1), on the Cu II ion doped compound of 1 (2), and on the Cu II ion doped compound in a Zn II matrix isomorphou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…However, the small values of the exchange constants are one order of magnitude larger than the hyperfine splitting of complex 5 in an MeCN/PFO mixture, and therefore appear to be enough to cause exchange narrowing of the EPR signals of the complex when this is aggregated in pure MeCN. The magnitude of the exchange coupling (∼0.1–0.2 cm −1 ) transmitted through π‐π interactions between the terpyridine ligands, is much smaller than the values found for systems where the magnetic centers are connected through extended covalent pathways, and even small compared to exchange couplings transmitted through pathways involving H‐bonds [30b] . These values are too small to be observed by standard magnetic measurements, and are usually only revealed by EPR spectroscopy, which is especially suitable to observe very small magnetic interactions.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…However, the small values of the exchange constants are one order of magnitude larger than the hyperfine splitting of complex 5 in an MeCN/PFO mixture, and therefore appear to be enough to cause exchange narrowing of the EPR signals of the complex when this is aggregated in pure MeCN. The magnitude of the exchange coupling (∼0.1–0.2 cm −1 ) transmitted through π‐π interactions between the terpyridine ligands, is much smaller than the values found for systems where the magnetic centers are connected through extended covalent pathways, and even small compared to exchange couplings transmitted through pathways involving H‐bonds [30b] . These values are too small to be observed by standard magnetic measurements, and are usually only revealed by EPR spectroscopy, which is especially suitable to observe very small magnetic interactions.…”
Section: Resultsmentioning
confidence: 71%
“…For complexes 3 and 5 , no hyperfine splittings could be observed, and the spectra resembled those of exchange‐narrowed extended magnetic systems (Figures 7 and 8). [30b,42] This phenomenon is suggestive of aggregation in solution, likely due to the F ${\cdots }$ F interactions of the PFC tails. To investigate this further, complexes 3 and 5 were measured in pentafluorobenzonitrile or a solution of acetonitrile/pentafluorobenzonitrile, respectively (Figure S24).…”
Section: Resultsmentioning
confidence: 99%
“…Least squares analysis of eq 3 to the data considering the chain model for the dipolar interaction are shown as solid lines in Figures 7; A 1 –A 7 parameters are given in Table 2. Least squares analysis to the data assuming the 3D model (second moment of the dipolar interaction) performed as explained elsewhere [27] yielded A 7 ‐coefficients less than the uncertainty of the method (∼0.1 mT) (not shown), which indicates that neither 1 nor 2 behave as 3D systems regarding the dipolar interaction. The good agreement between fitting and experimental data for 1 indicates a good correlation between magnetism and structure, i. e. structural and magnetic chains are the same.…”
Section: Resultsmentioning
confidence: 99%
“…19 The most common experimental techniques for characterising the electronic and magnetic properties of high spin Co( ii ) ions are spectroscopic methods such as UV-vis absorption, magnetic circular dichroism, paramagnetic nuclear magnetic resonance, electron paramagnetic resonance (EPR), and electron-nuclear double resonance, and magnetic techniques such as magnetic susceptibility and magnetisation measurements. 20–40 Characterisation of high spin Co( ii ) ion complexes in different coordination environments with these techniques showed that they present g-values for the S = 3/2 multiplet in the range of 2.1–2.8, and zfs usually greater than 50 cm −1 for hexacoordinated compounds, between 20–50 cm −1 for pentacoordinated compounds and less than 13 cm −1 for tetracoordinated compounds, 41 although some exceptions have been reported. 42–46 Furthermore, the exchange interactions that couple mononuclear Co( ii ) centres in extended lattices are usually below ∼3 cm −1 , and hence usually not detected or poorly discriminated with the most usual experimental techniques, with the only exception being EPR.…”
Section: Introductionmentioning
confidence: 99%